Relationship Between Service Quality and Patient Loyality In The Installation of Labuang Baji Hospital Makassar - Mangindara; Dian Ekawaty; Sriyani Windarti; Andi Nailah Amirullah; Nurul Azizyah Aksha (Miracle Journal of Public Health, 2023)
Service quality is measured by how well it meets the target audience's expectations. There seems to be some variation in the number of inpatients, as the number of re-hospitalized patients at Labuang Baji Makassar Hospital fell from 6,245 in 2019 to 5,448 in 2020 and 6,145 in 2021. The hospital is faced with a dilemma with the declining number of outpatient visits. The hospital's ability to operate and the quality of services provided to inpatients over the past year will be affected by the decrease in the number of patients treated at the hospital. Researchers at Labuang Baji General Hospital in Makassar set out to explore this question in order to better serve inpatients. This study used a cross-sectional descriptive quantitative research design. A total of 512 participants and 225 replies were included in the analysis. Bivariate analysis using Chi-Square test. With a p-value of 0.042 for professionalism and skill, a p-value of 0.042 for attitude and behavior, a p-value of 0.049 for reliability and trust, a p-value of 0.047 for service recovery, and p-value 0.027 for communication, this study found a correlation between service quality and patient loyalty. With a p value of 0.057, physical variables are considered unimportant. The conclusion in this study is that there is a relationship between professionalism and skill, attitude and behavior, reliability and trustworthiness, service recovery, communication with patient loyalty.